Analisis Isi Kurikulum Al-Qur’an Hadis di Madrasah Ibtidaiyah - Rani Yulisa; Muhammad Zuhdi; Bobi Erno Rusadi (Yayasan Al-Afif, 2025)
This study addresses the problem of Al-Qur’an Hadith learning at the Madrasah Ibtidaiyah (MI) level, which tends to emphasize textual mastery such as reading and memorization while lacking contextual and applicative understanding. The purpose of this research is to analyze the content of the Al-Qur’an Hadith curriculum at MI based on Decree of the Minister of Religious Affairs Number 347 of 2022 and to examine its relevance to educational objectives and students’ developmental characteristics. This study employs a qualitative descriptive approach using content analysis, with data collected through document analysis of official curriculum texts, policy documents, and relevant literature. The findings indicate that the curriculum is systematically structured and oriented toward basic competencies; however, its implementation is still predominantly textual. The study concludes that integrating learning theories and strengthening pedagogical approaches are essential to promote meaningful learning and internalization of Qur’anic values. These findings contribute to improving curriculum implementation and instructional practices in Islamic primary education.